HOW TO OVERCOME TEACHERS THE ANXIETY OF STUDENTS? - Nevedomsjka, Jevghenija O.; Mykhajlovsjka, Taisija O. (Educological discourse, 2016)
The article deals with the concept of "anxiety", a comparative analysis of the concepts of "anxiety," "anxiety," "fear," analyzed the scientific literature on anxiety problems, set goals and objectives of the pilot study disclosed method of the experiment. The study proved that the level of anxiety of the student depends on the type of temperament. Such data will be useful to teachers in the educational process. Recommendations teachers of higher educational institutions to optimize the level of anxiety of students.